Assessment of Media impact on changing oral health behaviors among university students in Kurdistan Region-Iraq - Abdulqadir, Mardin Othman; Hasan, Akam Mustafa; Rauf, Aras Maruf (Sulaimani Journal for Pure and Applied Sciences, 2018)
Media campaigns are generally used to deliver health messages to high number of populations through various types of Media. The Media is used in all aspects of public issues with the expectation of three influences; providing exact health information and relevant data, health behaviours and its value changes, and building new healthier behaviours. This study focused on the outcomes of massive Media campaigns and their effects on different hazardous oral.
Keywords: Media; Health programmes; Oral health; Behaviour; University students